2002
DOI: 10.1139/a02-009
|View full text |Cite
|
Sign up to set email alerts
|

Essentiality of nickel and homeostatic mechanisms for its regulation in terrestrial organisms

Abstract: Nickel (Ni) is a naturally occurring element with many industrial uses, including in stainless steel, electroplating, pigments, and ceramics. Consequently, Ni may enter the environment from anthropogenic sources, resulting in locally elevated concentrations in soils. However, Ni is a minor essential element, and, therefore, biota have established systems that maintain Ni homeostasis. This paper discusses the role of Ni as an essential element and reviews storage, uptake, and transport systems used to maintain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(29 citation statements)
references
References 220 publications
(316 reference statements)
0
28
1
Order By: Relevance
“…Data on Ni essentiality in insects are very limited in comparison with other micronutrients. On the other hand, broad spectrum of toxicity, transport, and interactions with other metals has been well documented (Phipps et al 2002). We showed that sap feeders had much lower Ni contents than the appropriate parts of their host plant ( Ni 100 lg g -1 ; K 2.5 wt.%; Ca 0.2 wt.%; Zn 500 lg g -1 ; Fe 500 lg g -1 .…”
Section: Discussionmentioning
confidence: 72%
“…Data on Ni essentiality in insects are very limited in comparison with other micronutrients. On the other hand, broad spectrum of toxicity, transport, and interactions with other metals has been well documented (Phipps et al 2002). We showed that sap feeders had much lower Ni contents than the appropriate parts of their host plant ( Ni 100 lg g -1 ; K 2.5 wt.%; Ca 0.2 wt.%; Zn 500 lg g -1 ; Fe 500 lg g -1 .…”
Section: Discussionmentioning
confidence: 72%
“…However, due to its high usage in industry and the involuntary anthropogenic release, this metal can reach high concentrations in soils [20], potentially disturbing the ecosystems' homeostasis. In previous studies using cell lines [21],d a p h n i d s [22] or fish [23],N i toxicity has been related to oxidative stress, a process commonly induced by metals, which reflects the imbalance between the production of reactive pro-oxidant species and the ability to neutralize their harmful effects.…”
Section: Hnmrmetabolomicsmentioning
confidence: 99%
“…Regarding Ni effects on soil invertebrates, the information available is still very scarce, being focused on bioaccumulation and mortality testing (e.g. [20,25]). Recently, our group has addressed the response of terrestrial isopods to long-term Ni exposure by measuring changes in energy reserves and the activity of detoxification enzymes [12].…”
Section: Hnmrmetabolomicsmentioning
confidence: 99%
“…Therefore, the presence of Ni hyperaccumulating plants appears to enhance the transfer of Ni from soil to herbivore and carnivore trophic levels. However, with the exception of hyperaccumulator plants, Ni does not biomagnify in the terrestrial foodweb [99], thereby its toxicity to higher trophic levels appears to be unlikely.…”
Section: Met Ions Life Sci 2 1-30 (2007)mentioning
confidence: 99%